A review on gender differences in dental anxiety - SIVARAJAN, MADHUMITHAA; LAKKOJI, DR.KEERTHISASANKA; DR. VENKATESH; EZHILARASAN, DR.DEVARAJ (The journal of contemporary issues in business and government, 2021)
The aim of this study is to review the gender differences in dental anxiety and the role a dentist plays in it, to assess those patients and treat them according and to make certain exceptions with patients with dental anxiety. Dental anxiety is a major hurdle when it comes to seeking advice in oral and dental problems. Dental pain and dental anxiety are the most common phobias among people. Pain is defined as an unpleasant sensation associated with sensory and emotional stimuli. Anxiety is due to emotion aroused by danger and pain because of distress. Toothache is one of the major causes which brings the patient to a dentist. Dental fear and anxiety are the two major factors that prevent patients from visiting a dentist. There is a common observation where patients only visit a dentist when there is severe Pain otherwise patients with dental anxiety don’t go to a dentist. Anxious patients suffer from inferior oral health than non - anxious patients. A review with recent information about gender differences in dental anxiety and its impact on dentists and patients from various search engines like medline, google scholar, bioRXIV, pubmed, chem RXIV, MESH etc. The recent articles discussed in this review helps in gaining knowledge about the gender differences in dental anxiety, how much the influence of anxiety has on patients who need dental treatment .Female patients wish to seek treatment and also have a higher level of anxiety whereas male patients avoid dental treatment because they are frightened about pain, their negative experience and in some cases, worried about the expense of a dental treatment. And in other cases, people do not think dental treatment is necessary at all and thus leading to improper oral hygiene.